Mad Science: 100 Amazing Experiments from the History of Science - Reto U Schneider (Quercus, 2009)
In Mad Science Reto Schneider tells the extraordinary tales of 100 of the more unusual experiments conducted across seven centuries of science. These are stories that are often bizarre, sometimes mind-boggling - occasionally stomach-churning - but always diverting, informative and enlightening.